Procedure Selecting Pumps Running as Turbines in Micro Hydro Plants. (September 2017) - Barbarelli, S.; Amelio, M.; Florio, G.; Scornaienchi, N.M.
Abstract: The authors present a combined method using statistical and numerical models for selecting a pump running as turbine in micro hydro plants. The data of the site (head and capacity) allow calculating two coefficients, CQ and CH, which identify the pump to use successfully as turbine in that place. A one dimensional model, starting from data available on the pumps manufacturers catalogues, reconstructs a virtual geometry of the PAT, then calculates the performances curves, head vs. capacity, efficiency vs. capacity. The procedure has been applied with the aim to select a PAT recovering energy from a pipeline whose characteristic curve is known.